Bimbingan dan Konseling Di Sekolah Dasar: Guru Kelas Berperan Penting dalam Implementasi Layanan - Vivi Astuti Nurlaily (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2019)
This study aims to describe the role of classroom teachers in carrying out guidance and counseling in elementary schools. This research is a qualitative descriptive study. The data source is a fourth grade elementary school teacher in SDN 4 Ngawen, Ngawen District, Blora Regency. Data analysis is carried out starting from the stage of data collection, data reduction, data presentation, and data verification. The result showed therole of the teacher had been going very well in terms of planning, implementation and evaluation. Class teachers understand the characteristics and abilities of each student, assist student in solving problems, teach the ability to behave and have social relations, assist student in developing learning disciplines. Forms of counseling guidance services carried out by classroom teachers in carrying out guidance and counseling in SDN 4 Ngawen among others personal guidance, social guidance, study guidance, and career guidance. This includes seven counseling, guidance services namely orientation service, information services, distribution and placement service, learning services, individual counseling services, group guidance and group counseling services.